Betydelsebeskrivningens förutsätningar i en enspråkig ordbok - Jonsson, Hans (LexicoNordica, 1994)
Monolingual dictionaries are by their very nature truly defining, unlike bilingual ( or multilingual) dictionaries, translation dictionaries. This article is mainly about the semantic basis of definition. Having distinguished in the lexicon of a natura! language lexical elements representing "languages within the language", that is, words which are provincial, socially and stylistically marked, as well as purely technical terminology, the author discusses the more uniform system of a standard language. The key concept is lexeme. A lexeme can correspond to a word in the traditional sense but can also correspond to a distinct use of a word. lgnoring the phenomenon of synonymy, a lexeme contrasts with every other lexeme. There are also elements of opposition in a more special sense. There are relatively often opposing pairs such as (in Swedish) fattig : rik; stor : liten; pojke : flicka; lärare : elev, besides which there are also fix.ed oppositions consisting of several elements, such as bäck : å : älv or sommar : höst : vinter : vår. A distinct hierarchical order on a small scale, in the form of "mini semantic fields" (such as the hyperonym vattendrag with its hyponyms bäck, å, älv) occurs in the lexicon. On the other hand, there does not appear to be any general hierarchical order for !arge lexeme spheres, much less for the entire lexicon. In fäet, there is probably no overall lexical structure which would be a full equivalent to grarnmatical and phonological structure. To put it in very general terms, the task of the lexicographer is to do justice to the linguistic division of the conceptual world by means of lexemes and to the elements of structure in the strict sense which the lexicon undoubtedly displays.